(untitled) (Asian Journal of Medical and Biological Research, 2015)
To evaluate the reproductive herd health status, the data were collected from Talbag Dairy Farm, Savar; Bangladesh Agricultural University Dairy Farm, Mymensingh and Central Cattle Breeding and Dairy Farm, Savar for a period of two years. A total of 122 lactating cows were selected to collect data on productive and reproductive performance from the farms record book maintained by three farms. The mean value ± SD of breeding age, calving age, age at first conception, calving to first estrus, calving to first service, days open, calving interval, first service conception rate, number of service per conception, calf per year of Talbag Dairy Farm, BAU Dairy Farm, Central Cattle Breeding and Dairy Farm were 25.10 ± 2.68, 219.23 ± 12.23 and 27.40 ± 7.56 months; 34.30 ± 8.54, 55.88 ± 11.60 and 38.93 ± 8.58 months; 26.20 ± 4.05, 52.71 ± 12.55 and 29.83 ± 8.72 months; 165.00 ±73.82, 219.23 ± 121.83 and 190.50 ± 104.19 days; 165.00 ±73.82, 240.77 ± 128.59 and 190.50 ± 104.19 days; 201.00 ± 72.48, 250.38 ± 72.82 and 335.08 ± 118.61 days; 383.30 ± 57.87, 526.44 ± 196.80 and 523.17 ± 216.37 days; 73.50 ± 29.25, 64.75 ± 30.53 and 61.85 ± 31.87 %; 1.95 ± 0.44, 1.99 ± 0.72 and 2.30 ± 1.02; 383.30 ±57.87, 526.44 ± 196.80 and 523.17 ± 216.37 days, respectively. The overall calf mortality (%) in Talbag Dairy Farm, BAU Dairy Farm, Central Cattle Breeding and Dairy Farm were 4%, 0.70% and 4.06%, respectively. The calf mortality (%) at birth and birth to 30 days in Talbag Dairy Farm, BAU Dairy Farm, Central Cattle Breeding and Dairy Farm were 3%, 1% and 1.85%; 3.5%, 5% and 6.39%; respectively. It is concluded that commercial farms reasonably better due to optimum level of breeding age, first service conception rate, less calving interval and less service per conception. Asian J. Med. Biol. Res. June 2015, 1(1): 31-38